Reliability of traditional and task specific reference tasks to assess peak muscle activation during two different sprint cycling tests - Kordi, M.; Folland, J.; Goodall, S.; Barratt, P.; Howatson, G. (Journal of Electromyography and Kinesiology, 2019)
Neuromuscular activation is considered an important determinant sprint cycling performance but requires reliable EMG amplitude measurements to facilitate sensitive assessments. The reliability of EMG measurements during sprint cycling may depend on the sprint cycling test undertaken (isovelocity or isoinertial accelerating), the reference tasks used for normalisation (isometric MVCs of a series of single muscle groups [ISO-SINGJT] or isometric cycling MVCs [ISO-CYC]), and the efficacy of the normalisation. This study aimed to compare the magnitude and between-session reliability of peak muscle activation (peak rmsEMG) during: isovelocity and isoinerital sprint cycling tests; ISO-SINGJT and ISO-CYC reference tasks; and absolute and normalised EMG during the sprint cycling tests.